What’s new in minimally invasive thoracic surgery? Clinical application of augmented reality and learning opportunities in surgical simulation - Onorati, Ilaria; Radu, Dana Mihaela; Martinod, Emmanuel (Frontiers in Surgery, 2023)
Lung cancer represents the most lethal cancer worldwide. Surgery is the treatment of choice for early-stage non-small cell lung cancer, with an overall survival that can reach 90% at 5 years, but its detection is difficult to achieve due to the lack of symptoms. Screening programs are crucial to identify small cancer. Minimally invasive surgery has modified the therapeutical approach of these tumors, becoming the standard of care, with an important clinical yield in terms of reduction of postoperative pain and length of hospital stay. The aim of this mini-review is to explore and describe two important and innovative aspects in the context of “growing opportunities in minimally invasive thoracic surgery”: the clinical application of augmented reality and its advantages for patient and surgeon, and the pedagogical issue through simulation-based training.